2015
DOI: 10.3109/21691401.2015.1089255
|View full text |Cite
|
Sign up to set email alerts
|

Real-time monitoring of mesenchymal stem cell responses to biomaterial surfaces and to a model drug by using quartz crystal microbalance

Abstract: In this study, the mesenchymal stem cell (MSC) responses to biomaterial surfaces and to an anti-microtubule drug (vinblastine) were detected by using the quartz crystal microbalance (QCM). Gold electrodes with different coatings were subjected to MSCs under flow conditions; thus, crystal frequency decreased due to the adhesion of MSCs on the crystal. For evaluation of cell-drug interactions, vinblastine was introduced to MSCs attached onto the surfaces. The changes in frequency indicated the binding of drug to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…The stability of AT-cut quartz under temperature change has led to a wide range of applications involving measurement of mass deposition in vacuum. TSM devices can operate in liquid and have been used for a variety of chemical or biosensor applications which include detection and analysis of proteins (serum, neurotransmitters) (Wang and Muthuswamy, 2008), antibodies as well as DNA (Ferreira et al, 2009; Li et al, 2011), self-assembled monolayer (SAMs) (Seker et al, 2016), lipids and cells (neurons, fibroblast, blood cells, neutrophils, bacteria) (Khraiche et al, 2003, 2005; Da-Silva et al, 2012; Khraiche and Muthuswamy, 2012; Zhou et al, 2012; Westas et al, 2015). The first attempts to study adhesion of cells using TSM sensors involved platelet adhesion (Matsuda, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…The stability of AT-cut quartz under temperature change has led to a wide range of applications involving measurement of mass deposition in vacuum. TSM devices can operate in liquid and have been used for a variety of chemical or biosensor applications which include detection and analysis of proteins (serum, neurotransmitters) (Wang and Muthuswamy, 2008), antibodies as well as DNA (Ferreira et al, 2009; Li et al, 2011), self-assembled monolayer (SAMs) (Seker et al, 2016), lipids and cells (neurons, fibroblast, blood cells, neutrophils, bacteria) (Khraiche et al, 2003, 2005; Da-Silva et al, 2012; Khraiche and Muthuswamy, 2012; Zhou et al, 2012; Westas et al, 2015). The first attempts to study adhesion of cells using TSM sensors involved platelet adhesion (Matsuda, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…These studies have indicated that the QCM cell biosensor is suitable for evaluating cell attachment in the early stage of TE. QCM successfully detected mesenchymal stem cell (MCS) responses to biomaterial surfaces [ 157 ]. Cell adhesion depends on the surface properties of the biomaterial, such as topography, wettability, charge, and protein adlayers.…”
Section: Potential Use Of Qcm In Cartilage Tissue Engineering (Cte)mentioning
confidence: 99%